Effect of Bacterial Invasion on the Growth and Lipid Production of the Oleaginous Yeast Rhodotorula glutinis - Harkins, Marianne; Lou-Hing, Daniel; Sargeant, Lisa A.; Chuck, Christopher J. (Journal of Technology Innovations in Renewable Energy, 2013)
Oleaginous microbes, grown heterotrophically on sugars derived from non-food crops or waste resources, are a renewable source of lipids. However, these cultures are prone to bacterial invasion. Ensuring optimal sterile conditions requires expensive pre-treatment techniques and has significant ramifications for the industrial-scale production of lipid derived biofuels, though, at present, it is unclear what effect a bacterial invasion would have on the organisms ability to accumulate lipid. In this investigation, the oleaginous yeast Rhodotorula glutinis (R. glutinis) was cultured under optimal conditions for lipid production (28 °C and pH 6.3) and the response to contamination by three common bacterial strains, Escherichia coli (E. coli), Pseudomonas fluorescens (P. fluorescens) and Bacillus subtilis (B. subtilis) was investigated. Bacterial strains were introduced to the yeast culture at 0, 4, 8, 12, 24 and 48 hours and their effect on the yeast growth and total lipid productivity was assessed. R. glutinis cultures that had been growing for less than 12 hours were unable to compete with any of the bacterial strains introduced. Lowering the temperature and pH allowed the yeast to compete more effectively, though it was found that these conditions were detrimental to the lipid productivity. The effect of invasion was also specific to the type of bacteria. P. fluorescens was found to be the most successful bacteria in competing with R. glutinis, while B. subtilis was found to be the least. Two common antibiotics, tetracycline and sodium metabisulfite were also investigated for their ability to limit the effect of a bacterial invasion.